Sistem Informasi Kalkulasi Zakat Pada Kantor Baitul Mal Kabupaten Bireuen Berbasis Android - Winar, Sri; Rizki Putra, Erifki; Muslem R., Imam (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
The technology that is currently developing at its fastest pace is information and telecommunications technology, which presents a wide selection of forms and literature from various sources by searching for data to add insight in the development of applications that are made. The calculation of zakat basically has provisions and formulas that have been determined based on the hadith and Al-Qur'an, so to improve services and make it easier for the community in terms of determining and calculating zakat it is necessary to develop a calculation system so that people can easily determine the amount of zakat that must be issued by each individual zakat payer. In this research, the development of the Zakat Calculation Information System uses the php programming language which has been bundled in the Eclipse application. The resulting application will be able to help society in general and especially Android-based smartphone users in terms of calculating zakat including zakat fitrah to zakat mal. Zakat is wealth that must be issued if it meets the conditions determined by religion, and is distributed to people who have been determined as well, namely the eight groups who are entitled to receive zakat. In this study the method that will be used to help analyze problems and deal with problems is field research and literature review. This application has complete zakat calculations which include Zakat Fitrah and Zakat Maal (Zakat Treasure) and this application can assist users in calculating zakat independently and knowing the function of each zakat